2021
DOI: 10.3389/fmed.2021.714619
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival Outcomes and Comparison of Different Treatment Modalities for Stage I-III Cervical Esophageal Carcinoma

Abstract: Purpose: To investigate the survival outcomes, prognostic factors and treatment modalities of stage I-III cervical esophageal carcinoma (CEC) patients using data from the Surveillance, Epidemiology, and End Results (SEER) database from the period 2004–2016.Methods: Patients with a histopathologic diagnosis of CEC were included. The primary endpoint was overall survival (OS). Univariate and multivariate analyses of OS were performed using Cox proportional hazards models, and OS was compared using the Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…To balance the enrolled patients and reduce the selection bias of baseline characteristics between the two groups, we performed a PSM analysis for covariates, including marital status, and the 2014 FIGO stage at a ratio of 1:10 for AC: SCC. The PSM analysis was conducted as described in our previous studies (14,15). A univariate analysis was employed using the cumulative incidence function (CIF) to determine the probability of each covariate and Gray's test to evaluate the difference between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To balance the enrolled patients and reduce the selection bias of baseline characteristics between the two groups, we performed a PSM analysis for covariates, including marital status, and the 2014 FIGO stage at a ratio of 1:10 for AC: SCC. The PSM analysis was conducted as described in our previous studies (14,15). A univariate analysis was employed using the cumulative incidence function (CIF) to determine the probability of each covariate and Gray's test to evaluate the difference between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off point for the age at diagnosis was set at 70-years old as adopted by other SEER studies (11,12). Classification of the other variables was assorted according to our previous studies (13,14).…”
Section: Data Processingmentioning
confidence: 99%
“…Surgical treatment still has a great risk of major complications and a high morbidity and mortality rate [18][19] . Recently, a retrospective study including 347 cervical esophageal cancer patients from the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database was done to investigate the survival and prognostic factors of different treatment modalities [20] . The study showed that no signi cant survival bene t was obtained from triple therapy with surgery over double therapy (median OS time: 31 months versus 20 months; P = 0.184).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce selection bias of baseline characteristics between the two groups, we performed a PSM analysis at a ratio of 1:1 for covariates, including marital status, race, tumor size, 2014 FIGO stage, RT, and CT by the R “ MatchIt ” package. The PSM analysis was performed as described in our previous studies [ 27 , 28 ]. Survival curves were estimated using the Kaplan–Meier analysis and compared with the log-rank test.…”
Section: Methodsmentioning
confidence: 99%